2021
DOI: 10.3390/nursrep11030059
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers’ Experiences and Views of Using Surgical Masks and Respirators, and Their Attitudes on the Sustainability: A Semi-Structured Survey Study during COVID-19

Abstract: A universal mask use was instituted in healthcare during COVID-19 pandemic in 2020. The extensive growth in the consumption of surgical masks and respirators brought new challenges. Healthcare workers had to get accustomed to wearing the facemasks continuously, raising concerns on the patient, occupational, and environmental safety. The aim of this study is to describe frontline healthcare workers and other authorities’ views and experiences on continuous use of surgical masks and respirators (facemasks) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…The facemask properties related to users comfort are important, some of which noted in our current study are: easy to breathe through material, material protects from splashes, non-breakable material of mask, odourless mask, soft and thin mask, biodegradable material, material that does not cause sweating, material that is reusable.Similar findings were observed in a study conducted by Venesoja A et al [15] In a study among medical university students it was found that the most common side effects were redness, dryness, and itching of the skin, and also appearance of rashes. [9] another study among healthcare workers reveal similar findings of adverse effects due to prolonged use of mask, headache being the most common complaint (n=245), followed by: skin breakdown (n=175), acne (n=182), impaired cognition (n=81).…”
Section: Discussionsupporting
confidence: 88%
“…The facemask properties related to users comfort are important, some of which noted in our current study are: easy to breathe through material, material protects from splashes, non-breakable material of mask, odourless mask, soft and thin mask, biodegradable material, material that does not cause sweating, material that is reusable.Similar findings were observed in a study conducted by Venesoja A et al [15] In a study among medical university students it was found that the most common side effects were redness, dryness, and itching of the skin, and also appearance of rashes. [9] another study among healthcare workers reveal similar findings of adverse effects due to prolonged use of mask, headache being the most common complaint (n=245), followed by: skin breakdown (n=175), acne (n=182), impaired cognition (n=81).…”
Section: Discussionsupporting
confidence: 88%
“…This may be due to the reuse of surgical masks for economic reasons and the use of reusable cloth masks. Healthcare workers are more likely to use disposable surgical masks on a daily basis (Venesoja et al 2021 ). Our data shows that non-healthcare workers are not using masks at the same rate.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas studies on sustainable consumption have been conducted, research on masks, especially in the context of COVID-19, remains limited. Existing studies have examined mask design, performance improvement, and production (Boix Rodríguez et al, 2021 ; Venesoja et al, 2021 ), but not consumer choice. Therefore, as the environmental pollution caused by disposable masks is severe, we examined variables that could motivate consumers to choose sustainable masks, which can help further research.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable masks, such as “The Joinery (made from recycled plastic bottles)” “Beta MSK (made from recycled water bottles),” and “Seeus 95(features a natural made of bamboo, silk and carbon)”, are produced to help solve the environmental problems associated with the use of disposable masks (Block, 2020 ; Gupta et al, 2021 ; Meisenzahl, 2020 ). Most previous studies focused on the design of masks for increased performance and convenience (Boix Rodríguez et al, 2021 ; Venesoja et al, 2021 ). However, research on the opinion of consumers regarding sustainable masks, remains scarce.…”
Section: Introductionmentioning
confidence: 99%